THE ROLE OF BLENDING THEORY IN POLYSEMY AND METAPHOR - Dalieva, Madina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Blending Theory offers a revolutionary perspective in cognitive linguistics, highlighting how innovation in language and thought stems from the integration of multiple conceptual spaces. This theory elucidates the cognitive mechanisms behind human creativity, providing a comprehensive framework for understanding the emergence of complex concepts, innovative metaphors, and the polysemous nature of language. Its application extends our insights into the dynamic nature of meaning-making and metaphorical thinking in human cognition.